2014
DOI: 10.1002/bies.201300104
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA binding sites in the coding region of mRNAs: Extending the repertoire of post‐transcriptional gene regulation

Abstract: It is well established that microRNAs (miRNAs) induce mRNA degradation by binding to 3' untranslated regions (UTRs). The functionality of sites in the coding domain sequence (CDS), on the other hand, remains under discussion. Such sites have limited impact on target mRNA abundance and recent work suggests that miRNAs bind in the CDS to inhibit translation. What then could be the regulatory benefits of translation inhibition through CDS targeting compared to mRNA degradation following 3' UTR binding? We propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(117 citation statements)
references
References 89 publications
(144 reference statements)
3
113
0
1
Order By: Relevance
“…4 D). Although most of the miRNA studies to date have been focused on the regulatory effect of miRNAs in the 3′ UTR of the target genes, it was well documented that miRNAs could also inhibit their target protein translation potentially through interfering with ribosome movement (Hausser et al, 2013;Brümmer and Hausser, 2014). Our luciferase reporter results confirmed that IL-4 is indeed a direct target of miR-24.…”
Section: Mir-23 Family Controls the Differentiation Of Multiple Th Cesupporting
confidence: 73%
“…4 D). Although most of the miRNA studies to date have been focused on the regulatory effect of miRNAs in the 3′ UTR of the target genes, it was well documented that miRNAs could also inhibit their target protein translation potentially through interfering with ribosome movement (Hausser et al, 2013;Brümmer and Hausser, 2014). Our luciferase reporter results confirmed that IL-4 is indeed a direct target of miR-24.…”
Section: Mir-23 Family Controls the Differentiation Of Multiple Th Cesupporting
confidence: 73%
“…It is important to note that while our results were based on analyses of reference 39 UTR targeting, recent work (Sandberg et al 2008;Brummer and Hausser 2014) suggests that both alternative polyadenylation and miRNA targeting outside of 39 UTRs may alter miRNA regulation to pathophysiological effects. Incorporating these lines of evidence may help further our understanding of miRNA regulation, and we believe that these challenges can be addressed using current technology.…”
Section: Discussionmentioning
confidence: 98%
“…For example, statistical evidence suggests that expression profiles of ESR1-regulating miRNAs are predictive of variability in the coupling between ESR1 mRNA and protein-expression profiles. Moreover, a study focusing on the ability of individual miRNA to predict coupling of target mRNA and protein-expression profiles may help identify miRNAs that primarily regulate translation and those that regulate mRNA destabilization (Brummer and Hausser 2014).…”
Section: Discussionmentioning
confidence: 99%
“…They participate in translation repression [2]. Previously, miRNA binding sites were predicted only at the 3'UTR [3], but recently it is known that these sites are also located at the 5׳- untranslated regions (5׳UTRs) [4] and coding sequences (CDSs) of mRNAs [5]. Therefore, it is of interest to identify miRNA encoded oligo-peptides that are conserved across evolutionary distance.…”
Section: Introductionmentioning
confidence: 99%